Doenças raras: o que o pediatra necessita saber - Maria Goretti Moreira Guimarães Penido; Maria Helena Vaisbich; Lilian Monteiro Pereira Palma; Nilzete Liberato Bresolin (Residência Pediátrica, 2024)
Rare disease or an orphan disease is a disease that affects a small percentage of the population. Most of these diseases are present throughout the patients life, even if the symptoms do not appear immediately. They are often fatal or chronically debilitating and the impact on the quality of life of patients and their families is significant. Patients with rare diseases often experience delays in diagnosis, which can negatively impact management and delay treatment. Familial genetic testing or cascade genotyping of all newly diagnosed individuals can speed up the diagnosis of these diseases and allow more patients to be identified at a younger age. Care for patients with chronic and rare diseases is complex, mainly due to lack of knowledge about the disease, which makes accurate and early diagnosis difficult, in addition to the need to perform specific tests, which are sometimes highly complex and costly. Added to these factors are difficulties in obtaining adequate treatment when available, raising awareness of the patient and family about the disease and adherence to treatment.A multidisciplinary approach is very important: care provided by a doctor, nurse, psychologist, nutritionist and social worker. These professionals, in addition to medical care, address the particularities of the disease and treatment, the impact on the life of the patient and his family, the approach to psychological and social issues, and guidance regarding medications and diets.